MAPPING THE LANDSCAPE OF STEAM EDUCATION (2021–2025): A BIBLIOMETRIC ANALYSIS OF MEDIA, LEARNING OUTCOMES, AND ASSESSMENT PRACTICES - Muhammad Sholihul Huda; Barokah Isdaryanti; Ellianawati; Fahrur Rozi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study maps the state of science, technology, engineering, arts, and mathematics education from 1 January 2021 to 16 October 2025 by synthesizing research on instructional media, learning outcomes, and assessment practices. The objective is to identify dominant trends, gaps, and implications to guide classroom innovation and evaluation. Articles were located in Scopus, Google Scholar, and Crossref and screened using a process modeled on PRISMA. From 1,375 records, 168 met the inclusion criteria after duplicate removal, relevance screening, and full-text checks focused on classroom practice, media integration, and outcome measurement. Methods combined a systematic review with bibliometric mapping of annual output, venues, co-authorship, keyword co-occurrence, and methodological features. Results show steady growth, peaking in 2024, and five clusters: primary education, media development and validation, learning-outcome testing, analytical approaches, and digital engagement. Quantitative achievement testing remains prevalent, while formative and performance-based assessments and measures of digital literacy and higher-order thinking gain momentum. The review concludes that enhanced technology, student-centered designs are reshaping practice and recommends media-rich tasks, clear rubrics, and longitudinal, comparable assessment frameworks. Keywords: assessment practices, bibliometric analysis, instructional media, learning outcomes, primary education, steam education